Isolation and characterization of α ‐amylase encoding gene in Bacillus amyloliquefaciens PAS - Achmad Rodiansyah; Sitoresmi Prabaningtyas; Mastika Marisahani Ulfah; Ainul Fitria Mahmuda; Uun Rohmawati (Universitas Gadjah Mada, 2021)
Amylolytic bacteria are a source of amylase, which is an essential enzyme to support microalgae growth in the bioreactor for microalgae culture. In a previous study, the highest bacterial isolate to hydrolyze amylum (namely PAS) was successfully isolated from Ranu Pani, Indonesia, and it was identified as Bacillus amyloliquefaciens. That bacterial isolate (B. amyloliquefaciens PAS) also has been proven to accelerate Chlorella vulgaris growth in the mini bioreactor. This study aims to detect, isolate, and characterize the PAS’s α‐amylase encoding gene. This study was conducted with DNA extraction, amplification of α‐amylase gene with polymerase chain reaction (PCR) method with the specific primers, DNA sequencing, phylogenetic tree construction, and protein modeling. The result showed that α‐amylase was successfully detected in PAS bacterial isolate. The α‐amylase DNA fragment was obtained 1,468 bp and that translated sequence has an identity of about 98.3% compared to the B. amylolyquefaciens α‐amylase 3BH4 in the Protein Data Bank (PDB). The predicted 3D protein model of the PAS’s α‐amylase encoding gene has amino acid variations that predicted affect the protein’s structure in the small region. This research will be useful for further research to produce recombinant α‐amylase.